Effects of the Norfolk diabetes prevention lifestyle intervention (NDPS) on glycaemic control in screen-detected type 2 diabetes: a randomised controlled trial - Michael Sampson; Allan Clark; Max Bachmann; Nikki Garner; Lisa Irvine; Amanda Howe; Colin Greaves; Sara Auckland; Jane Smith; Jeremy Turner; Dave Rea; Gerry Rayman; et al. (BMC Medicine, 2021)
Abstract Background The purpose of this trial was to test if the Norfolk Diabetes Prevention Study (NDPS) lifestyle intervention, recently shown to reduce the incidence of type 2 diabetes in high-risk groups, also improved glycaemic control in people with newly diagnosed screen-detected type 2 diabetes. Methods We screened 12,778 participants at high risk of type 2 diabetes using a fasting plasma glucose and glycosylated haemoglobin (HbA1c). People with screen-detected type 2 diabetes were randomised in a parallel, three-arm, controlled trial with up to 46 months of follow-up, with a control arm (CON), a group-based lifestyle intervention of 6 core and up to 15 maintenance sessions (INT), or the same intervention with additional support from volunteers with type 2 diabetes trained to co-deliver the lifestyle intervention (INT-DPM). The pre-specified primary end point was mean HbA1c compared between groups at 12 months. Results We randomised 432 participants (CON 149; INT 142; INT-DPM 141) with a mean (SD) age of 63.5 (10.0) years, body mass index (BMI) of 32.4 (6.4) kg/m2, and HbA1c of 52.5 (10.2) mmol/mol. The primary outcome of mean HbA1c at 12 months (CON 48.5 (9.1) mmol/mol, INT 46.5 (8.1) mmol/mol, and INT-DPM 45.6 (6.0) mmol/mol) was significantly lower in the INT-DPM arm compared to CON (adjusted difference −2.57 mmol/mol; 95% CI −4.5, −0.6; p = 0.007) but not significantly different between the INT-DPM and INT arms (−0.55 mmol/mol; 95% CI −2.46, 1.35; p = 0.57), or INT vs CON arms (−2.14 mmol/mol; 95% CI −4.33, 0.05; p = 0.07). Subgroup analyses showed the intervention had greater effect in participants < 65 years old (difference in mean HbA1c compared to CON −4.76 mmol/mol; 95% CI −7.75, −1.78 mmol/mol) than in older participants (−0.46 mmol/mol; 95% CI −2.67, 1.75; interaction p = 0.02). This effect was most significant in the INT-DPM arm (−6.01 mmol/mol; 95% CI −9.56, −2.46 age < 65 years old and −0.22 mmol/mol; 95% CI −2.7, 2.25; aged > 65 years old; p = 0.007). The use of oral hypoglycaemic medication was associated with a significantly lower mean HbA1c but only within the INT-DPM arm compared to CON (−7.0 mmol/mol; 95% CI −11.5, −2.5; p = 0.003). Conclusion The NDPS lifestyle intervention significantly improved glycaemic control after 12 months in people with screen-detected type 2 diabetes when supported by trained peer mentors with type 2 diabetes, particularly those receiving oral hypoglycaemics and those under 65 years old. The effect size was modest, however, and not sustained at 24 months. Trial registration ISRCTN34805606 . Retrospectively registered 14.4.16